Effect of Nd:YAG and Er:YAG laser tooth conditioning on the microleakage of self-adhesive resin cement - Azita Kaviani; Niloofar Khansari Nejad (Biomaterial Investigations in Dentistry, 2021)
Statement of problem Recently, the application of lasers in restorative dentistry has been considered for cavity preparation and surface conditioning of enamel and dentin. However, the beneficial effects of cavity surface conditioning by laser irradiation on microleakage are still controversial. Purpose This study aimed to compare the microleakage of self-etch adhesive resin cement with Nd:YAG and Er:YAG laser tooth surface conditioning to evaluate the capabilities of these lasers as a reliable replacement for etching cavities. Materials and methods Fifty-four class V cavities were prepared on the buccal and lingual surfaces of 27 sound human premolar teeth. The samples were randomly divided into three groups (n = 18): group 1: no conditioning; group 2: conditioned with Er:YAG laser (2940 nm, 10 Hz, 1.2 W); group 3: conditioned with Nd:YAG laser (1064 nm, 1.5 W, 10 Hz). All the cavities were filled with self-adhesive resin cement. After curing and polishing, the samples were immersed in 2% methylene blue solution for 24 h, and after being embedded in acrylic resin, they were sectioned longitudinally and examined under a stereomicroscope. The data were submitted to Kruskal–Wallis and Dunn tests (α = 0.05). Results The lowest microleakage mean rank was observed in the Er:YAG group (19.19), and the highest mean rank was noted in the Nd:YAG group (33.08), with significant differences between the three groups (P-value = .01). Pairwise comparisons demonstrated significant differences between the Er:YAG and Nd:YAG groups (P-value = .004) as well as Er:YAG and no conditioned groups (P-value =.022). Conclusion The irradiation of the Er:YAG laser (2940 nm, 10 Hz, 1.2 W) on cavity surface resulted in less marginal microleakage of self-etch adhesive resin cement restorations compared to Nd:YAG (1064 nm, 1.5 W, 10 Hz) and no conditioning groups.